The Invisible War - Dick, Kirby; Johnson, Kirsten; Wadleigh, Thaddeus (New Video, 2012)
From Oscar and Emmy-nominated filmmaker Kirby Dick comes "The Invisible War", a groundbreaking investigative documentary about one of America's most shameful and best-kept secrets: the epidemic of rape within the U.S. military. The film paints a startling picture of the extent of the problem - today, a female soldier in combat zones is more likely to be raped by a fellow soldier than killed by enemy fire. Twenty percent of all active-duty female servicewomen are sexually assaulted. Profoundly moving, the film follows the stories of several idealistic young servicewomen who were raped and then betrayed by their own officers when they courageously came forward to report. Both a rallying cry for the hundreds of thousands of men and women who've been assaulted and a hopeful road map for change, "The Invisible War" is one of those rare films so powerful it has already helped change military policy. [Cover]